Blow-up rate for parabolic problems with nonlocal source and boundary flux - Arnaud Rougirel (Electronic Journal of Differential Equations, 2003)
We determine the blow-up rate and the blow-up set for a class of one-dimensional nonlocal parabolic problems with opposite source term and boundary flux. As a consequence, it is shown that the solutions approach negative infinity in the interior of the domain and positive infinity at one boundary point.